The dynamics of large inflation surges - Andrés Blanco; Pablo Ottonello; Tereza Ranošová (Federal Reserve Bank of Atlanta, 2024)
We empirically characterize episodes of large inflation surges that have been observed worldwide in the last three decades. We document four facts. (1) Inflation surges tend to be persistent, with the duration of disinflation exceeding that of the initial inflation increase. (2) Surges are initially unexpected but followed by a gradual catch-up of average short-term expectations with realized inflation. (3) Long-term inflation expectations tend to exhibit increases that persist throughout disinflation. (4) Policy responses are characterized by hikes in nominal interest rates but no tightening of real rates or fiscal balances. In sum, episodes of large and persistent inflation tend to occur with government responses that depart from the prescriptions of textbook policy rules, and that instead exhibit a "fear of tightening.
Keywords: E31; E40; F40; 330; inflation surges; inflation expectation; fiscal and monetary policy